Compliance to hand hygiene and its determinant factors among Community Health Care Providers in Community Clinics: an observational study in Bangladesh. Issue 2 (March 2022) - Rahman, Md Hafizur; Hassan, Md Nazmul; Khan, Md Shafiqul Islam; Hasanuzzaman, Md; Awal, Nurullah
Background: Healthcare-associated infections caused by poor hand hygiene (HH) practices can affect both the care seekers and the health care providers (HCPs) while providing primary health care. No study has been conducted on the compliance of HH practices among the primary level HCPs in Bangladesh. Objective: The study aimed to assess the compliance rates of HH and its determinant factors among Community Health Care Providers (CHCPs) in Community Clinics (CC). Methods: A cross-sectional study was conducted from September 2019 to February 2020 among 150 randomly selected CHCPs with functional HH facilities in Patuakhali district, Bangladesh. Structured interviews and observation tools were used to collect data. Results: Good HH compliance among CHCPs was found to be 16.7% (95% CI: 11.3–21.3). Out of all 1218 possible HH opportunities, only 255 (20.9%) resulted in any HH action. Presence of 70% alcohol-based hand sanitiser at the point of care (aOR: 6.4, 95% CI: 1.1–38.3), HH training (aOR: 4.6, 95% CI: 1.1–18.9), displayed visual cues (aOR: 4.4, 95% CI: 1.1–17.7), knowledge about HH (aOR: 3.8, 95% CI: 1.1–13.6) and number of HH opportunities (aOR: 0.6, 95% CI: 0.4–0.8) were factors associated with HH compliance. Discussion: Overall HH compliance among CHCPs was relatively low. It was recommended to implement multimodal HH improvement strategies, including a continuous training program, supply of alcohol-based hand rub, reminder, provision of five moments of HH in the training modules and feedback on HH performance.